Temperature and Salinity Monitoring System for Shrimp Pond Water - Zalvi, Rahmat Gilang; Basrah Pulungan, Ali (Journal of Industrial Automation and Electrical Engineering, 2025)
Shrimp pond productivity is highly dependent on water quality, which is traditionally monitored manually through labor-intensive sampling and testing. This study proposes an IoT-based smart monitoring system to automate the assessment of water quality parameters such as temperature and salinity. The system employs an ESP32 microcontroller integrated with DS18B20 and salinity sensors. Sensor data are displayed in real time via a 4x20 LCD and the Blynk application. Two relays are included to automatically activate the aerator when temperature defined thresholds. Field testing over four days demonstrated sensor accuracy with error rates below 3%, stable data transmission, and effective automation. This system offers a reliable and efficient solution for shrimp farmers to monitor and manage water quality, potentially enhancing aquaculture productivity.